Is It T3 Thyrotoxicosis? A Case of Falsely Elevated Tri-Iodothyronine (T3) Levels Leading to a Diagnosis of Multiple Myeloma - Nanik Ram; Saira Furqan; Sibtain Ahmed (Case Reports in Endocrinology)
We are presenting a case of falsely elevated T3 levels in a patient due to interference from monoclonal immunoglobulins. A 56-year-old, clinically euthyroid man referred to the endocrinology clinic of the Aga Khan university, Karachi Pakistan, for possible T3 thyrotoxicosis after thyroid function tests revealed total T3 >12.32 nmol/L (reference range 0.6–2.79), normal TSH, and total T4 level. There was a mismatch in clinical and laboratory parameters and preliminary laboratory results were suggestive of thyroid binding globulin abnormalities. Further evaluation in this context unmasked multiple myeloma. The presence of monoclonal immunoglobulins can lead to assay interference and spurious results. To the best of our knowledge, this is the second case defining the cause of falsely elevated T3 levels, due to assay interferences with binding of T3 only to monoclonal immunoglobulins.